Peran Pemanasan Menggunakan Teknik Scale Mayor dan Minor Terhadap Pembelajaran Instrumen Piano Bagi Anak-Anak - Sekar Aurellia Septi Priatna Fian Priatna (TAMUMATRA, 2024)
The development of the times has made many changes in society. If in the past music was considered contrary to the surrounding culture, the situation is different now. At this time the existence of music is very important, because it can provide stimulation for children to be creative through the art of music. The use of music will make children more free in expressing or expressing their feelings. Schools are also starting to provide music learning materials, although in practice this is not free from the challenges they face. Whether it's from teachers who don't have a music background, or the process of digesting children or students who are different. Therefore, to start piano learning activities, a warm-up is carried out using major and minor scale techniques. The aim is for each child to practice their piano playing, while also flexing their fingers; wrist; elbow; as well as shoulders. Qualitative methods were used to study this problem. So we came to the conclusion that the role of warming up using major and minor scale techniques is to support their learning process when studying music